Impacto de contaminações por bactérias láticas em processos produtivos de etanol e métodos de controle microbiológico - Santos, Andriele Fátima da Silva (Universidade Federal de São Carlos, 2025)
Ethanol production in Brazil occurs predominantly through alcoholic fermentation, with the Melle-Boinot process being particularly noteworthy. This process relies on the reuse of yeast between fermentation cycles, contributing to greater production efficiency. However, due to large-scale operation and the absence of completely aseptic conditions, the process becomes susceptible to microbiological contamination. Lactic acid bacteria are one of the main interfering factors, as they compete with the yeast Saccharomyces cerevisiae for the sugars in the must and produce undesirable metabolites, such as organic acids, which compromise cell viability and ethanol yield. In this context, microbiological monitoring is essential for the early detection of deviations, although conventional methods have limitations related to precision and manual execution. In parallel, traditional control strategies, such as acid treatment and the use of antibiotics, while effective, act predominantly in a corrective manner and present disadvantages associated with environmental impacts, operational risks, and the development of microbial resistance. In this context, the CIP (Cleaning-in-Place) system stands out as a preventive hygiene approach, allowing the cleaning of industrial equipment without the need for disassembly, contributing to the reduction of microbial load, the prevention of recurrent contamination, and greater stability of the fermentation process. This work aimed to analyze the impact of lactic acid bacteria on ethanol production, discuss methods of microbiological monitoring and control, and evaluate the role of the CIP system as a preventive strategy, through an exploratory literature review based on scientific articles, books, and technical documents. Therefore, it is concluded that the integration between microbiological monitoring and the proper use of the CIP system favors the control of contamination, promoting improvements in industrial performance, productivity, and the sustainability of ethanol production.
Impact of lactic bacterial contamination on ethanol production processes and microbiological control strategies
Keywords: fermentação alcoólica; etanol; contaminação microbiana; bactérias láticas; CIP; ENGENHARIAS::ENGENHARIA QUIMICA::TECNOLOGIA QUIMICA; 9. Indústria, Inovação e Infraestrutura; 12. Consumo e Produção Responsáveis